First Sighting Record of Black-necked Grebe Podiceps nigricollis from Chhattisgarh, India - Sharan, Lokesh; Thakur, Pratik (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
On 14th December 2024, a Black-necked Grebe (Podiceps nigricollis) was observed at Kopra Dam, Bilaspur district, Chhattisgarh, marking the first recorded occurrence of this species in the region. The bird, identified based on its distinct morphological features, was photographed and compared with standard literature for confirmation. This sighting expands the known wintering range of the species in India and highlights the importance of Kopra Dam as a potential habitat for rare migratory birds.